Cardiac Arrhythmia Simulations for Comparing Remote Telemetry Monitoring Systems. Issue 1 (June 2018) - Segall, Noa; Franklin, Ron'Nisha; Wright, Melanie C.
To increase the potential for timely detection of cardiac events, hospitalized patients who are at risk for critical arrhythmias are put on telemetry to continuously monitor their heart rhythm. However, telemetry monitoring systems vary widely between hospitals, there are few guidelines for decisions regarding optimal practices, and few studies have compared the efficiency of different monitoring systems. Our goal was to determine the impact of different monitoring systems on the time to detect and respond to critical cardiac events. To this end, we compared the process of communicating a critical alarm to the patient's nurse in 2 hospitals with different monitoring systems, to determine the most efficient system. We conducted in situ unannounced simulations of cardiac arrest in the 2 hospitals to measure the response times of monitor watchers and patient care unit staff. As expected, we found response times to be shorter in the hospital that had a more direct method for monitor watchers to contact patients' nurses. In addition to the method for communicating arrhythmias, there are many other differences between the monitoring systems in the 2 hospitals that could also have affected response times. We are using discrete event simulation to develop computer simulation models of the hospitals that will allow us to take multiple factors into account when comparing them.